Agrifood trade in Tajikistan - Khakimov, Parviz; Ashurov, Timur; Aliev, Jovidon; Goibov, Manuchehr (International Food Policy Research Institute, 2025)
Despite being an agrarian economy, Tajikistan heavily relies on agrifood imports. Agrifood imports have increased sharply in recent years, while export growth has been modest. This brief outline the key trends in Tajikistan’s agrifood trade and provides policy recommendations to reduce import dependence and boost domestic agricultural production. Key trends in agrifood trade • Between 2000 and 2023, Tajikistan’s agrifood imports grew 16 times, with vegetable products (primarily cereals) and prepared foodstuffs (sugar, animal fodder, flour, oil) accounting for 83 percent of total imports. • While imports have surged, agrifood exports have grown by only 2.2 times during the same period. Exports remain concentrated in a few products, with dry fruits and nuts making up 75 percent of total agrifood exports in 2023. • Processed food imports have significantly increased, reflecting both changing consumer preferences and domestic production gaps. This shift, particularly in urban areas, underscores the growing role of imports in meeting demand for food products beyond basic staples. • Tajikistan’s agrifood imports and exports are dominated by trade with Commonwealth of Independent States (CIS) countries. These long-standing trade ties reflect logistical advantages and shared histories. However, this reliance on a narrow set of trading partners limits the potential to access new, more lucrative markets. Recommended actions • Tajikistan needs to focus on modernizing its agricultural sector to raise productivity and lessening the country’s reliance on imports. • Strengthening Tajikistan’s agrifood processing sector will help reduce the growing dependency on processed food imports. Investments in food processing infrastructure and the promotion of local agribusinesses could meet the rising demand for processed products. • Diversifying the range of exported agrifood products is crucial. Developing processing industries and value added products can help reduce dependency on a few commodities and open doors to new export markets. • While CIS countries are important trading partners, Tajikistan should explore opportunities to expand market access outside the region. Improving the quality of agrifood exports and meeting international standards will enable the country to participate in more global value chains and trade agreements.